Model Pembelajaran Kooperatif Tipe TGT dan Pengaruhnya Terhadap Hasil Belajar PAI - Aina Noviana (UIN Sunan Gunung Djati Bandung, 2022)
The purpose of this study was to determine: 1) The application of the Teams Games Tournament type of cooperative learning model, 2) The effect of the Teams Games Tournament type of cooperative learning model on student learning outcomes in PAI subjects. This study uses a quantitative approach with a quasi-experimental research method in the form of a nonequivalent control group design. Data collection techniques used are observation and tests. Based on the results of the study, it showed that: 1) The implementation of the Teams Games Tournament type of cooperative learning model was 84.6%, categorized as good; 2) Teams Games Tournament type cooperative learning model has an influence on student learning outcomes in Islamic Religious Education subjects of 6.42 with a low increase of 0.15.